Current status of blood 'pharming': megakaryoctye transfusions as a source of platelets. Issue 6 (November 2017) - Gollomp, Kandace; Lambert, Michele P.; Poncz, Mortimer
Abstract : Purpose of review: Donor-derived platelets have proven to be of hemostatic value in many clinical settings. There is a fear that the need for platelets may outgrow the donor pool in first-world countries. Moreover, there are other challenges with donor platelets that add to the impetus to find an alternative platelet source, especially after the megakaryocyte cytokine thrombopoietin was identified. Megakaryocytes have since been differentiated from numerous cell sources and the observed released platelet-like particles (PLPs) have led to calls to develop such products for clinical use. The development of megakaryocytes from embryonic stem cell also supported the concept of developing nondonor-based platelets. Recent findings: Several groups have claimed that nondonor-based platelets derived from in-vitro grown megakaryocytes may soon become available to supplement or replace donor-derived products, but their number and quality has been wanting. A possible alternative of directly infusing megakaryocytes that release platelets in the lungs – similar to that recently shown for endogenous megakaryocytes – has been proposed. Summary: This present review will describe the present state-of-the-art in generating and delivering nondonor-derived platelets. Progress has been slow, but advances in our ability to generate human megakaryocytes in culture, generate PLPs from these cells, and test the functionality of the resultant platelets in vitro and in vivo have identified important remaining challenges and raised alternative potential solutions.